Daniel Sierra - VoxelMorph based Normalization in the Prediction of Stable VS Progressive MCI Conversion with Convolutional Neural Networks - Sierra, Daniel (Jornada de Jóvenes Investigadores del I3A, 2022)
VoxelMorph based Normalization in the Prediction of Stable VS Progressive MCI Conversion with Convolutional Neural Networks